Design of a fuel-efficient scheme for space debris removal. Issue 1 (1st May 2022) - Hu, Wenjun; Yang, Yueneng
Abstract: In view of the growing threat of space debris and the limitation of current debris removal method. A novel conceptual solution for multiple space debris removal is proposed, and a low-cost and miniaturized removal system is designed in this paper. And the structural composition of this removal system is designed and the space debris removal process is introduced, the system can be divided into two components including satellite platform and many mission CubeSats. The mission CubeSats can be re-launched into the transfer orbits of different space debris through a push-launch method, and the fuel consumptions on the removal mission for three space debris, using the proposed multiple removal system and traditional removal system are calculated and compared. The compared results demonstrated that the proposed solution for multiple space debris removal and the designed removal system can decrease the fuel consumptions effectively.